PERANAN SANTRI DALAM MENGELOLA KEBERSIHAN LINGKUNGAN ASRAMA DI PONDOK PESANTREN DR.M.NATSIR ALAHAN PANJANG KABUPATEN SOLOK - fitrina, Leli; Ahmad, Ridwan; Yuherman, Yuherman (Pendidikan Geografi, 2013)
The study aimed to obtain information,Â  date analyze about the role of students in managing environment hygiene dormitory in the boarding school DR.M.Natsir. who views of how the role of students in creating and maintaining the cleanlines hostel environment.This is qualitative study using interview techniques. To answer this problem used primary date and secondary date. Primary date obtained from observation, interviews with informants they are students in boarding school DR.M.Natsir and documentation, while secondary date obtained from the relevant parties.The result showed: 1 the role of student in creating a healty environment at the school dormitory DR.M.Natsir Alahan Panjang is defined as something that should inplemented as if it hasbeen created hygiene, the environment will be healtheir, we willbespared from disease, living in the dorm would be fun, through activities which can create a cleaner environment, such as mutual cooperation, dispose of waste in place which is provide, but students knowledge about creating hygiene are not in accordance with their behaviour towarde environment cleanliness.2. the role of students in a dormitory done keeping the in environment by cleaning sewer water, obey and follow the rules of the builder, clean room as well as providing guidance to actions other students when the student keep the environment less. But in dealing with all of that, studen just do a simple manner, such as gutter cleaning water only once, obey the rules and runt it at the picket alone, clean room just by sweeping, but cleaning the room of glass and window clean only when the dust have many ar thick.